Ayurvedic Management of Recurrent Pregnancy Loss Due to Diminished Ovarian Reserve- A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
The problem of infertility is increasing day by day due to current scenario of fast stressful and imbalanced life style. Infertility is defined as the failure to conceive after one year of regular unprotected coitus. Conception depends on the fertility potential of both the male and female partner. Ovulatory dysfunction, tubo-peritoneal factors, uterine factors, cervical and immunological factors, low ovarian reserve etc. contribute to female infertility or delayed conception. Ayurveda classics discussed the topic elaborately under the heading Vandhyata along with its Nidana (etiology), Samprapthi (etiopathogenesis), Bheda (types) and Chikitsa (treatments). According to Ayurveda infertility refers to the biological inability of a women of reproductive age group to conceive and unable to carry pregnancy to full term. Normal status of Garbha sambhava samagri, normal fuction of Vata, and Soumanasya are inevitable for Garbhadharana. This is a case report of 24year old female suffered from infertility due to recurrent pregnancy loss. Patient has hypothyroidism, diminished ovarian reserve and low AMH. Ayurveda IP and OP management including Ama pachana, Agni deepana, Sodhana karma, Samana karma etc., were adopted and patient conceived and delivered a healthy child. This article presented with recurrent pregnancy loss due to ovarian and uterine factors along with treatment approach in a view to explore for future research